BIOGEOGRAPHICAL STUDIES OF VENEZUELAN SPECIES OF STYLOSANTHES (LEGUMINOSAE) - CALLES, Teodardo; SCHULTZE-KRAFT, Rainer; GUENNI, Orlando (Acta Botánica Venezuelica, 2017)
Stylosanthes is a mainly Neotropical genus comprising ca. 25 species with Venezuela hosting high species richness. Despite of the economic importance of some species as forage legumes, the biogeography of Stylosanthes in Venezuela has hitherto been poorly studied. Information of herbarium specimens and germplasm accessions was collated in order to assess distribution, range size, geographic species richness and rarity in the country. Stylosanthes guianensis has the widest geographical distribution and the largest range size. The highest species richness occurs in the eastern plains (“Llanos”) (7-10° N, 62-65° W). The endemic S. sericeiceps and S. venezuelensis fall within the rarest category. This study contributes to better understand the pattern of biogeographical variation of Venezuelan Stylosanthes species, and can help to design conservation strategies.